Motion planning for gait rehabilitation robotic - Aung, Thu Myint (2012)
In modern technology, rehabilitation devices are used to train the patients suffering from stroke to get back their normal walking ability by forming new neural connections. Hence, neuronal circuits of stroke patients that have been affected by brain lesion will be retrained, resulting in improving motor control. However, the current rehabilitation devices use the treadmill training method to train the walking ability. According to previous researches and experiments, subjects training with treadmill ambulation had a shorter stance time, higher cadence, larger hip range of motion (ROM) and greater maximum hip flexion angle. Therefore, those robotic rehabilitation devices using treadmill may not provide the natural walking patterns of a person during training.